Implementation of Geographic Information System for Hotels and Lodging in Asahan Regency - Salsabila, Adinda; Nurwati, Nurwati; Sena, Maulana Dwi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Asahan Regency is one of the regencies located in North Sumatra. There are hotels and inns scattered at several points in Asahan Regency. Visitors from outside Asahan Regency and local residents still do not know the distribution points. It is still difficult to find out the closest route to hotels and inns. This will make visitors confused about the location of the hotel. So with that, a system is needed that can facilitate tourists and the government in Asahan Regency, especially the Youth, Sports and Tourism Office, to provide accurate information and promotional tools about the location of hotels and inns to help visitors find the right accommodation. That is by creating a Geographic Information System for Hotels and Lodging in Asahan Regency by utilizing the Google Maps API which displays information related to the location of hotels and inns as well as detailed hotel and inn information such as addresses, hotel prices and other information and also displays information about the Asahan Regency Youth, Sports and Tourism Office.